Exploring new methods for teaching and learning human geography - Ye, Chao (Springer, 2024)
This book proposes a new and central teaching concept "we are all makers" and innovates the geographical teaching modes and methodology. Geography teaching, especially how to teach geographical thinking, is important and related to the development of the discipline. In this field, the exploration of new teaching methods in non-English speaking countries and regions still needs to grow. Based on the author's experience of teaching geographical thinking and human (cultural) geography for more than ten years, the book links geographical thinking to the realistic cases with new social media tools such as WeChat APP and blog. Under the guidance of these new methods, such as poem, emotional, couplet game, keywords, blog-based teaching, and the like, students are transformed from passive recipients of knowledge to active learners and even creators in the end. The book, which focuses on and pioneers new teaching methodology or methods, is used as a reference by scholars, researchers, practitioners, and readers specialized in fields such as geography, education, and pedagogy